An integrated analysis of China's iron and steel industry towards carbon neutrality. (15th September 2022) - Wang, Xiaoyang; Yu, Biying; An, Runying; Sun, Feihu; Xu, Shuo
Highlights: Develop a cost-optimal model towards carbon neutrality in the iron and steel industry. Explore the cost-effective carbon neutral pathway in the iron and steel industry. Promoting energy-saving technologies is the most effective strategy to reduce CO2 . Stable scrap supply would assist carbon neutrality in the iron and steel industry. Abstract: The iron and steel industry is a critical sector for achieving China's carbon neutrality goal. However, existing studies lack considering the multiple constraints including limited resources, technology diffusion and carbon emissions reduction on design of carbon neutral pathway for iron and steel industry. A broader analysis that can integrate resources-technologies-emissions in to a united framework is necessary. To further explore the feasible paths and challenges faced by the iron and steel industry, this study developed the C 3 IAM/NET-IS (China's Climate Change Integrated Assessment Model/National Energy Technology-Iron and Steel) model to select the optimal technology portfolios. By incorporating 11 measures such as technological innovation, structure adjustment of raw material, clean energy, etc., the integrated impact on CO2 emissions, energy consumption, raw materials, and costs is analyzed, while the carbon neutral pathway for the iron and steel industry is further investigated. The results show that CO2 emissions of China's iron and steel industry would peak at about 1514.14–1530.86 million tonnes before 2023. And there would be more than 72.78 million tonnes of CO2 in 2060, requiring carbon sinks to absorb to achieve carbon neutrality. During 2020–2060, the most effective measure would be the promotion of energy-saving technologies, which would contribute about 22.07% of CO2 emission reduction. Compared to the EAF (Electric Arc Furnace) with 50% scrap, promoting EAF with 100% scrap would result in cumulative total costs savings of about 4361.04 billion CNY while consuming 15.14 billion tonnes of scrap. To coordinate the goals of carbon neutrality and raw material security, it is necessary to support domestic iron ore enterprises through tax relief and to accelerate the large-scale construction of the scrap recycling industry.